Analysis of Factors Related to Nutritional Status in Toddlers with Stunting - Naomi Maria Welmince Ado; Retno Widowati; Risza Choirunissa (Griya Eka Sejahtera, 2026)
Background: Stunting is a condition in which toddlers are shorter than average for their age. Stunting is a serious nutritional problem. This condition can have serious impacts on children's physical, cognitive, and social development, as well as on the quality of human resources in the future. This study aimed to analyze factors related to nutritional status in toddlers with stunting.Methods: This study employed a quantitative approach with a cross-sectional analytical design. The sample size was 30 stunted toddlers aged 3-5 years, using a cluster sampling method. A questionnaire was used as the research instrument. Primary data were analyzed using the chi-square statistical test.Results: The results of the Univariate analysis showed that 90% of toddlers were not LBW, 76.7% did not do IMD, 56.7% of toddlers did not receive exclusive breastfeeding, 96.7% of toddlers did not have ISPA, 50% of toddler mothers had low education, 80% of family income was ≤UMR and 86.7% of families followed CHLB. The results of the bivariate analysis showed that there was a significant relationship between LBW and nutritional status in stunted toddlers (p value = 0.014), while other independent variables did not have a significant relationship.Conclusion: Analysis of the relationship between low birth weight (LBW) p = 0.014 shows a statistically significant relationship. Analysis of the relationship between Early Breastfeeding Initiation (EBI), Exclusive Breastfeeding, Acute Respiratory Infection (ARI) incidence, Mother's Education Level, Family Income, and the implementation of Clean and Healthy Living Behaviors (CHLB) with the nutritional status of stunted infants in this study showed no significant relationship, indicating that the provision of EBF to the study participants did not directly influence the nutritional status of stunted infants.